Screening of Lactic Acid Bacteria Isolated from Foods for Interference with Bacterial Quorum Sensing Systems - Dimitra Kostoglou; Efstathios Giaouris (Biology and Life Sciences Forum, 2025)
Quorum sensing (QS) is a cell-to-cell communication mechanism through which microorganisms can sense their population density and adjust their physiology by producing and detecting small signaling molecules called autoinducers (AIs). QS influences various aspects of microbial physiology, including virulence and pathogenesis by bacterial pathogens, biofilm formation, sporulation, antimicrobial resistance, etc. Lactic acid bacteria (LAB) have been used for centuries in food fermentation to improve sensory and nutritional profiles and preserve against spoilage and pathogenic microflora. This study investigated the potential of foodborne LAB of various genera, including Lactococcus, Lactobacillus, Leuconostoc, Streptococcus, and Enterococcus, to interfere with the QS system of bacterial pathogens. For this, cell-free supernatants (CFSs) of 89 LAB foodborne isolates were collected by centrifugation following a 20 h culture (at 30 °C) in quarter-strength Brain Heart Infusion (BHI) broth. The pH of all CFSs was adjusted to 6.5 and sterilized by filtration. The anti-QS activity of the sterilized and neutralized CFSs was initially screened using the biosensor strains Chromobacterium violaceum 026 and Agrobacterium tumefaciens NTL4 (pZLR4) through an agar well diffusion assay that can detect the inhibition of the QS system that is based on acylated homoserine lactones (AHLs), which are used as AIs by Gram-negative bacteria. Additionally, all the CFSs were also screened for interference with the autoinducer 2 (AI-2) QS system that is mostly used for interspecies communication by both Gram-positive and Gram-negative bacteria. This was assessed using a luminescence bioassay with the Vibrio harveyi BAA-1117 biosensor strain. The results indicate that none of the LAB CFSs could inhibit AHL-based QS. However, 61.8% (55/89) of the CFSs induced luminescence in V. harveyi BAA-1117, while the remaining 38.2% (34/89) of the samples were capable of inhibiting AI-2-based QS. In the next steps, the most representative of these latter AI-2 interfering LAB isolates will be investigated for possible inhibition of biofilm formation by some important foodborne bacterial pathogens.